A Behavioral Approach to Financial Supervision, Regulation, and Central Banking - Khan, Ashraf (IMF Working Papers; Working Paper ;, 2018)
This paper describes how behavioral elements are relevant to financial supervision, regulation, and central banking. It focuses on (1) behavioral effects of norms (social, legal, and market); (2) behavior of others (internalization, identification, and compliance); and (3) psychological biases. It stresses that financial supervisors, regulators, and central banks have not yet realized the full potential that these behavioral elements hold. To do so, they need to devise a behavioral approach that includes aspects relating to individual and group behavior. The paper provides case examples of experiments with such an approach, including behavioral supervision. Finally, it highlights areas for further research.